RSI and voluntary dismissal planes: trajectories of pain and suffering among bank employees (Cadernos de Psicologia Social do Trabalho, 2009)
The article presents the results obtained from a study conducted in 2002 with employees of a state-owned bank at Ribeirão Preto, SP, who were affected by Repetitive Strain Injuries (RSI). The investigation aimed at learning about what determined the onset of the disease and the effects of RSI on those employees' lives and work. 10 bank employees (6 females and 4 males) at ages 41 to 49 were interviewed. The selection of participants considered two criteria: a) being a bank employee with a clinical diagnosis which was compatible with RSI developed during professional practice and who had or had not taken a sick leave from work for that reason; b) being at or continuing working for the bank when the study was carried out. To all respondents, RSI meant a mark in their trajectories of life and work. It was evident that not only their professional activities were compromised, but so were various others in their daily lives and out of the work environment, such as household, personal-care, free-time, leisure activities. The new technologies adopted by banks, if on one hand optimized bank work and increased productivity, the efficiency of the services rendered and the profit of the industry, on the other, altered work conditions and affected bank employees' health. According to the data obtained, it was possible to perceive how the Voluntary Dismissal Plans were used as a instrument of pressure against workers. All the bank employees interviewed who issued a official work accident communication changed their positions at work after the RSI diagnosis.